A patient-derived and patient-reported outcome measure for assessing psoriatic arthritis: elaboration and preliminary validation of the Psoriatic Arthritis Impact of Disease (PsAID) questionnaire, a 13-country EULAR initiative. Issue 6 (30th April 2014) - Gossec, Laure; de Wit, Maarten; Kiltz, Uta; Braun, Juergen; Kalyoncu, Umut; Scrivo, Rossana; Maccarone, Mara; Carton, Laurence; Otsa, Kati; Sooäär, Imre; Heiberg, Turid; Bertheussen, Heidi; et al.
Abstract : Introduction: The objective was to develop a questionnaire that can be used to calculate a score reflecting the impact of psoriatic arthritis (PsA) from the patients' perspective: the PsA Impact of Disease (PsAID) questionnaire. Methods: Twelve patient research partners identified important domains (areas of health); 139 patients prioritised them according to importance. Numeric rating scale (NRS) questions were developed, one for each domain. To combine the domains into a single score, relative weights were determined based on the relative importance given by 474 patients with PsA. An international cross-sectional and longitudinal validation study was performed in 13 countries to examine correlations of the PsAID score with other PsA or generic disease measures. Test–retest reliability and responsiveness (3 months after a treatment change) were examined in two subsets of patients. Results: Two PsAID questionnaires were developed with both physical and psychological domains: one for clinical practice (12 domains of health) and one for clinical trials (nine domains). Pain, fatigue and skin problems had the highest relative importance. The PsAID scores correlated well with patient global assessment (N=474, Spearman r=0.82–0.84), reliability was high in stable patients (N=88, intraclass correlation coefficient=0.94–0.95), and sensitivity to change was also acceptable (N=71, standardised response mean=0.90–0.91). Conclusions: A questionnaire to assess the impact of PsA on patients' lives has been developed and validated. Two versions of the questionnaire are available, one for clinical practice (PsAID-12) and one for clinical trials (PsAID-9). The PsAID questionnaires should allow better assessment of the patient's perspective in PsA. Further validation is needed.